Determinan Gangguan Kapasitas Fungsi Paru Pada Pekerja Mebel di Kabupaten Gowa Provinsi Sulawesi Selatan - Ramadan, Fitrah; Hidayat, Sri Nurul; Lilis, Lilis; Syahrir, Nuruf Afrah; Akila, Nur; Ekasari, Ranti; Adnan, Yudi; Azwar, Muhammad; Widiastuty, Lilis (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
The furniture industry has a high economic value and competitiveness, 80% of all furniture production in Indonesia uses wood as raw material. In the process of producing wood into furniture, it will produce pollution, namely particles of wood dust. Wood dust can cause lung function disorders. This study was conducted to determine the determinants of lung function capacity disorders among furniture workers in Gowa Regency. Analytic survey, using a cross sectional approach. This study was conducted in the furniture industry in the Gowa Regency area in December 2023. The population in this study were all workers who worked in the furniture industry totaling 33 people. The sample in this study were 33 workers in the production section with total sampling. The instruments of this research are spirometer, nose clip and questionnaire. The results of this study indicate there is a relationship between smoking habits (p-value = 0.007) and the use of PPE (p-value = 0.013) with impaired lung function capacity. While the length of exposure (p-value = 0.674) which means there is no relationship with impaired lung function capacity. The variables of smoking habits and the use of PPE have a significant relationship with impaired lung function capacity, while the length of exposure does not have a significant relationship with impaired lung function capacity among furniture workers in Gowa Regency. Suggestion: implementing work rotation for workers and providing direction to workers about safe work procedures and according to standards, one of which is the use of PPE as an effort to control the risk of impaired lung function capacity in furniture workers in Gowa Regency.